Healthcare Branding and Reputation Management Strategies for Organizational Success - Durmus Senyapar, Hafize Nurgul (Technium Social Sciences Journal, 2024)
This study searches into the critical aspect of branding and reputation management within the dynamic view of the healthcare industry. This research aims to provide actionable insights for healthcare organizations to navigate the complexities of building and maintaining a strong brand identity by comprehensively analyzing the multifaceted aspects of healthcare branding, including its foundational principles, strategies, challenges, and opportunities. The research problem centers on identifying gaps and challenges in current healthcare branding and reputation management practices, recognizing the pressing need for systematic examination within evolving patient expectations, competitive pressures, and regulatory environments. This study offers a nuanced understanding of these critical areas through a structured exploration of healthcare branding’s fundamental significance, strategies employed for reputation management, and identifying existing challenges and opportunities. Drawing upon Brand Equity Theory, which underscores the value of a brand beyond solid assets, the study explains the role of brand equity in shaping patient perceptions, organizational success, and overall health outcomes within the healthcare context. Furthermore, the research outlines future avenues for investigation, including the impact of emerging technologies, longitudinal assessments of branding initiatives, data-driven insights, ethical considerations, and collaborative co-creation strategies. This study aims to advance knowledge and practice in healthcare branding and reputation management by addressing these areas and empowering healthcare organizations to enhance patient experiences, organizational performance, and public health outcomes in an ever-evolving healthcare view.